Synergistic antihyperglycemic effect of alpha lipoic acid with antidiabetic agents in the normoglycemic and streptozotocin-induced type 2 diabetic rats - Rawsan Ali Sabri; Basim Jasim Hameed; Falah Hassen Shari (Polskie Towarzystwo Farmaceutyczne, 2023)
The current study's main goal was to assess the supplementation effect of alpha lipoic acid with antidiabetic medications (metformin and sitagliptin) on normal and streptozotocin-induced blood glucose levels in normal and streptozotocin-induced diabetic rats. For this purpose, forty-two rats were randomly divided into two groups: normal control (n = 6) and diabetic (n = 36) groups, which were submitted to the following treatments: A: normal rats; B: diabetic rats; C: diabetic rats with sitagliptin (1 mg/kg); D: diabetic rats with metformin (10 mg/kg); E: diabetic rats with alpha lipoic acid (10 mg/kg); F: diabetic rats with a combination of alpha lipoic acid and sitagliptin; G: diabetic rats with a combination of alpha lipoic acid and metformin. The glycemia of these animals was monitored weekly; the use of alpha lipoic acid resulted in a significant decrease in glycemic levels. Combining alpha lipoic acid with either metformin or sitagliptin is most effective for reducing blood glucose levels in animals with acute and chronic hyperglycemia, even at different treatment times. Thus, associated with either metformin or sitagliptin, alpha lipoic acid improved their anti-diabetic effects.